Aerosol-assisted preparation of spherical AgBr nanoparticles with strengthened photocatalytic activity - Hao Sun; Shen Wang; Hao Zhu; Shuqi Li; Yazhou Kong; Jinquan Wang (Next Materials, 2024)
A type of spherical AgBr nanoparticles was synthesized using the aerosol-assisted precipitation method. The influence of solution mixing mode and polyvinylpyrrolidone on the morphology and photocatalytic activity of AgBr was investigated. The results demonstrate that both the aerosol-assisted precipitation method and the addition of polyvinylpyrrolidone surfactant effectively reduce the particle size of AgBr, leading to an enhancement in its specific surface area. Furthermore, the presence of polyvinylpyrrolidone surfactant promotes uniformity in shape and reduces size distribution variability among AgBr particles. These characteristics contribute to an improved photocatalytic performance, thereby expanding the potential applications for AgBr nanoparticles.